The level of cyber ethnocentrism among multi ethnic in Malaysia / Abdul Rauf Ridzuan, Jusang Bolong and Al-Mansor Abu Said - Ridzuan, Abdul Rauf; Bolong, Jusang; Abu Said, Al-Mansor (Division of Research and Industrial Linkages, 2017)
Ethnocentrism is the evaluation of other cultures according to preconceptions originating in the standards and customs of one's own culture. As Malaysians are practicing multicultural communication, ethnocentrism is there. This study is done in order to find the level of ethnocentrism among multiethnic SNS users in Malaysia. This study used the social capital theory as foundations theories for model development. The minimum sample size was determined through G⃰Power analysis. The study involved 482 respondents, selected through a cluster sampling technique involving three main ethnics in Malaysia. A cross sectional survey and structured questionnaire were used for data collection. All variables were measured through scales previously used by other researchers. SPSSS ver. 20 software was used in the analysis. Results of the SPSS indicated that for the level of ethnocentrism namely stereotype, mistrust, avoidance and differential treatment in SNS are low